SERUM MBL 2 WITH RISK GENOTYPING (RS1800450/CODON 54) IN SCHIZOPHRENIA PATIENTS: A HOSPITAL BASED STUDY IN SOUTHERN ODISHA (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Schizophrenia is a chronic psychiatric disorder characterized by delusions, hallucinations, cognitive deficits, and social dysfunction. Emerging evidence indicates that immune system dysregulation, particularly involving components of the innate immune system such as Mannose-Binding Lectin 2 (MBL2), may contribute to the pathogenesis of schizophrenia. Genetic variations, particularly at codon 54 of the MBL2 gene, may affect serum levels and influence disease susceptibility. Aims: Estimation and Correlation of routine biochemical parameters and serum MBL2 level with MBL gene polymorphism (codon 54; rs1800450) in cases with schizophrenia and in healthy controls. Methodology: A cross-sectional study was conducted taking 60 diagnosed patients of schizophrenia and age- and sex-matched 40 healthy controls. Serum MBL2 levels were assessed using ELISA kit, genotyping was done using RT- PCR and RFLP. Data were analysed using IBM SPSS 22. Results: Serum MBL2: lower in schizophrenia patients (244.03 ± 220.0 ng/mL) compared to controls (330.17 ± 243.2 ng/mL, p = 0.003). The analysis of MBL2 gene polymorphism showed AA, AB and BB genotypes 42 (70.0%), 13 (21.67%), and 5 (8.33%) in cases respectively whereas AA, AB and BB genotypes were found in 27 (62.50%), 12 (35.0%) and 1 (2.50%) in controls. Total cholesterol and triglycerides levels were significantly different among the above genotypes while HDL and LDL did not show any difference. Conclusion: This study explores the link between MBL2 level with risk genotype (homozygous BB variety) which alter the innate immunity, may serve as a potential biomarker for screening and risk prediction for the schizophrenia spectrum disorders.